Exproling Students' Perspective of The Use Audio-Visual in English Listening Skill - Nur Rahma Maulida M; Munir; Geminastiti Sakkir (International Journal of Language, Education, and Literature, 2025)
Developing listening skills in learning English as a foreign language poses several challenges, particularly when using audio-visual media. This study investigates the obstacles encountered by students during the learning process. Based on data collected from six Grade XI students at SMAN 2 Pangkep through non-participant observation, semi structured interviews, and documentation, the findings reveal four main types of obstacles. Linguistic barriers include difficulties in understanding vocabulary and various English accents. Technical obstacles involve problems such as poor device quality or unstable internet connectivity. Cognitive challenges emerge when students struggle to maintain focus or process the information effectively. Additionally, environmental factors, such as noise or other distractions in the learning environment, further hinder comprehension. These challenges significantly affect students' ability to engage with audio-visual materials and highlight the need for supportive strategies in enhancing listening skills.